Duhaldea pterocaula (Franch.) Anderb. Attenuates Nociception and Inflammation via GABAA Receptors - Huang, Chunli; Dong, Changsheng; Zhu, Yanan; Yu, Yang; Jin, Huizi; Zhang, Yan (Frontiers in Pharmacology, 2021)
Inula pterocaula Franch (I. pterocaula) is a folk medicine of the Yi nationality in China. The Inula plants display various biological activities, including anti-nociceptive and anti-inflammatory properties. I. pterocaula has been traditionally used for the treatment of bronchitis, vasculitis and dizziness. However, very few pharmacological studies on I. pterocaula have been reported. The present study aims to characterize the anti-nociceptive and anti-inflammatory properties of I. pterocaula and explored its underlying mechanism. I. pterocaula was extracted by 95% EtOH and further portioned with petroleum ether (PE), ethyl acetate (EA) and n-BuOH to obtain three factions with different polarities. The EA fraction (IPEA) was found to be one of the most effective fractions. IPEA demonstrated potent analgesic effects in both acute and inflammatory pain mouse models, and caused no antinociceptive tolerance. Furthermore, IPEA could improve the tolerance of mice to morphine. IPEA also showed potent anti-inflammatory effects on LPS-induced septic mice. BIC, a GABAAR could reverse the effects of IPEA in pain and inflammation models. Collectively, GABAARs play a key role in the pharmacological effects of IPEA. I. pterocaula may be useful as complementary or alternative therapeutic agent for the treatment of pain and inflammation.